Nickel(II) complex of 4-amino-N-(2-pyrimidinyl)benzenesulfonamide: Synthesis, spectroscopic characterization, antimicrobial activity, crystal structure, and Hirshfeld surface analysis. Issue 2 (1st February 2017) - Tailor, Sanjay M.; Patel, Urmila H.
ABSTRACT: A nickel complex of 4-amino-N-(2-pyrimidinyl)benzenesulfonamide (sulfadiazine) has been synthesized and characterized by elemental analysis, infrared, UV-Vis, and 1 H NMR spectroscopy. The title compound, [Ni(C10 H9 N4 O2 S)2 (C5 H5 N)2 ](C5 H5 N)(H2 O)2 crystallizes in monoclinic system with space group P 21 and Z=2. X-ray analysis revealed that Ni(II) ion exhibits a distorted octahedral geometry. The Hirshfeld surfaces are performed to study the nature of interactions and their quantitative contributions toward crystal packing. The results of spectral and thermal data suggest that the binding of nickel atom to the sulfonamidic nitrogen is in agreement with the crystal structure determination. Nickel sulfadiazine presents different antibacterial behavior against Escherichia coli and Staphylococcus aureus strains.